Microsomal metabolism of N-benzyl-N-ethylaniline and N-benzyl-N-ethyl-p-toluidine - (:unkn) unknown (Walter de Gruyter GmbH, 1997)
The in vitro hepatic microsomal metabolism of two tertiary anilines, N-benzyl-N-ethylaniline (NBNEA) and N-benzyl-N-ethyl-toluidine (NBNEPT), was examined in order to determine whether these compounds produce amide derivatives (benzoyl or acetyl) in addition to N-dealkylation and N-oxidation products as metabolites. The preparation of these tertiary anilines and their corresponding potential metabolites was undertaken. The amines and metabolites were separated using TLC and HPLC. Incubations were performed using hamster microsomal preparations fortified with NADPH. The substrates and their potential metabolites were extracted into dichloromethane and examined by TLC and HPLC. The metabolic process of particular interest was the formation of amides from NBNEA and NBNEPT. The results from these experiments indicated that neither tertiary aniline (NBNEA and NBNEPT) produced amide (acetyl or benzoyl) or N-oxide metabolites. These substrates were dealkylated to the corresponding secondary amines via debenzylation and de-ethylation. Uncharacterised metabolites observed with substrates are proposed to be phenolic (for NBNEA) and hydroxymethyl (for NBNEPT). These findings support the concept that: nitrones are essential intermediates for the formation of amides from secondary aromatic amines (chemical rearrangement to amide via an oxaziridine intermediate); carbinolamines produced by NBNEA and NBNEPT are not stable enough to allow further oxidation to amides and therefore these intermediates are broken down to dealkylated products. The results are discussed in relation to the mechanism of metabolic amide formation from amines.
Keywords: Dealkylation; Debenzylation; In vitro metabolism; Tertiary benzylic amines